Legal Protection of Consumer Data of a Personal Nature within the Framework of His Digital Banking Transactions: Analytical Study in UAE Legislation - Aouataf Zerara; Benhamla Sami (Journal of Legal Sciences, 2024)
The subject of legal protection of consumer data of a personal nature within the framework of his digital banking transactions constituted a very important subject in view of the digital transformation that modern banking life has witnessed, which produced a new type of contract represented in digital banking transactions, and this constituted a new challenge for banking legislation as well as consumer protection legislation. In addition the consumer personal data protection legislation. This study aims to demonstrate the extent to which modern banking legislation, modeled on the UAE legislator, has approved effective legal protection of consumer data of a personal nature in order to enhance his legal status and protect his privacy within the framework of his digital banking transactions, in a way that serves the development of these transactions and consumer protection. Considering that the UAE legislator subjects the protection of consumer data of a personal nature within the framework of his digital banking transactions to banking legislation as special provisions, this study raises questions about the reason for the UAE legislator adopting this approach and the justifications for that in light of the presence of provisions related to the protection of personal data. This study addressed the scope of protecting consumer data of a personal nature within the framework of their digital banking transactions and the controls for their use on the one hand, and on the other hand it addressed a statement of consumer rights in the field of using their banking data and the restrictions and violations associated with them.